1985
DOI: 10.1093/cvr/19.10.636
|View full text |Cite
|
Sign up to set email alerts
|

 -adrenoceptor density and relative number of  -adrenoceptor subtypes in biopsies from human right atrial, left ventricular, and right ventricular myocard

Abstract: In the present study we estimated the relative number of beta-adrenoceptors in membrane preparations from right atrial and left ventricular biopsies from 8 patients, as well as from right ventricular biopsy from one patient. Determinations of relative number of beta adrenoceptor subtypes (beta1, beta2) were also performed. Estimations were performed in a radioligand assay, measuring specific binding of [125I]-cyanopindolol (CYP). Inhibition of specific [125I] CYP binding was studied by adding propranolol (non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
1

Year Published

1987
1987
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 0 publications
2
19
0
1
Order By: Relevance
“…The affinity of the ligand for P-adrenoceptors in the slidemounted sections was similar to that found in homogenate binding studies ofhuman atria (Brodde et al, 1983;Heitz et al, 1983;Robberecht et al, 1983;Stiles et al, 1983;Golf et al, 1985;Hedberg et al, 1985) and cardiac P-adrenoceptors of other animal species (McPherson et al, 1984). The receptor density (Bmax) was also similar in sections and in some homogenate binding studies of human atria (Robberecht et al, 1983;Stiles et al, 1983;Golf et al, 1985;Hedberg et al, 1985), yet half that found in other studies (Brodde et al, 1983;Hedberg et al, 1985).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The affinity of the ligand for P-adrenoceptors in the slidemounted sections was similar to that found in homogenate binding studies ofhuman atria (Brodde et al, 1983;Heitz et al, 1983;Robberecht et al, 1983;Stiles et al, 1983;Golf et al, 1985;Hedberg et al, 1985) and cardiac P-adrenoceptors of other animal species (McPherson et al, 1984). The receptor density (Bmax) was also similar in sections and in some homogenate binding studies of human atria (Robberecht et al, 1983;Stiles et al, 1983;Golf et al, 1985;Hedberg et al, 1985), yet half that found in other studies (Brodde et al, 1983;Hedberg et al, 1985).…”
Section: Discussionsupporting
confidence: 79%
“…The percentage of P2-adrenoceptors in atrial sections was higher than that in some studies (20-26%) (Brodde et al, 1983;Heitz et al, 1983;Stiles et al, 1983;Golf et al, 1985) but less than that in others (50-55%) (Robberecht et al, 1983;Hedberg et al, 1985).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Patients with hyperthyroidism often develop atrial arrhythmias because the atria are more sensitive than the ventricles to the effect of thyroid hormones. 9,10 This preferential atrial arrhythmogenic effect of thyroid hormones seems to be caused by various factors such as atrialadrenergic receptor density 11 or differences between atrial and ventricular autonomic innervation and differences in sensitivity. 4 However, hyperthyroidism associated with organic heart disease or marked heart failure can cause malignant arrhythmias, including ventricular tachycardia and fibrillation.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular cloning of an individual cardiac ion channel has provided important new information on the molecular basis of cardiac excitability. The preferential atrial arrhythmogenic effect of thyroid hormones could also be caused by the increased atrial ␤-adrenergic receptor density (14) in the presence of reduced parasympathetic tone (15,16). Thus, it is conceivable that ␤-adrenergic blockade might reduce the arrhythmogenic effect of thyroid hormone in patients predisposed to supraventricular tachycardia, when L-T 4 treatment is considered indispensable.…”
Section: Discussionmentioning
confidence: 99%